2016
DOI: 10.1039/c6tc04553g
|View full text |Cite
|
Sign up to set email alerts
|

Stability, electronic structures and thermoelectric properties of binary Zn–Sb materials

Abstract: The composition–structure–property relationship of a complex high-performance thermoelectric system, Zn–Sb compounds, is systemically investigated by first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Previous studies on ZnSb have shown that both LDA and GGA underestimate the electronic band gap 3,12 . To avoid this problem, meta-GGA or hybrid functionals can be used 12,13,14 . In this study, two meta-GGA functionals: mBJ 15,16 and SCAN 17 have been tested.…”
Section: B Details Of the Calculationsmentioning
confidence: 99%
“…Previous studies on ZnSb have shown that both LDA and GGA underestimate the electronic band gap 3,12 . To avoid this problem, meta-GGA or hybrid functionals can be used 12,13,14 . In this study, two meta-GGA functionals: mBJ 15,16 and SCAN 17 have been tested.…”
Section: B Details Of the Calculationsmentioning
confidence: 99%
“…Apart from their intriguing structural diversity, interest in Zn–Sb phases has surged since the successful synthesis and promising thermoelectric characterization of numerous binaries, including Zn 4 Sb 3 , ZnSb, and Zn 8 Sb 7 . A computationally derived convex hull of formation enthalpies for various binary zinc antimonides predicts ZnSb to have the most negative formation enthalpy . Low-temperature, soft chemistry techniques may provide a reproducible means of observing and isolating many of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] A computationally derived convex hull of formation enthalpies for various binary zinc antimonides predicts ZnSb to have the most negative formation enthalpy. 36 Low-temperature, soft chemistry techniques may provide a reproducible means to observe and isolate many of these compounds. Computational surveys of antimony-based Zintl phases have revealed intriguing ternary compositions such as LiZnSb, KAlSb4, and KSnSb.…”
Section: Introductionmentioning
confidence: 99%
“…Ar), [34] or melt-spun preparation, [42] or compositingZ n 4 Sb 3 with nanostructures, [17] etc. [29,43] In this study,w ep ropose au seful tool using in situ high-resolution transmission electron microscopy (TEM) combined with high-quality compositional analysis to provide ad etailed understanding of the TE properties of nanostructured materials. [29] This could result from an unknown structural behaviour that was not clearly understood previously.…”
Section: Introductionmentioning
confidence: 99%